Recovery of cognitive function after relapse in multiple sclerosis. (January 2021) - Benedict, Ralph HB; Pol, Jeta; Yasin, Faizan; Hojnacki, David; Kolb, Channa; Eckert, Svetlana; Tacca, Beth; Drake, Allison; Wojcik, Curtis; Morrow, Sarah A; Jakimovski, Dejan; Fuchs, Tom A; et al.
Background: Cognitive impairment is common in multiple sclerosis (MS) but its manifestation as acute disease activity is underappreciated. Objective: The aim of this study is to examine recovery after MS relapse on multiple tests of cognitive and motor function and explore correlates of change with Expanded Disability Status Scale (EDSS), magnetic resonance imaging (MRI), and cognitive reserve. Methods: Fifty relapsing group (RG) and matched stable participants were examined at baseline, during relapse, and at 3-month follow-up. Tests of cognitive processing speed (Symbol Digit Modalities Test (SDMT)) and consensus opinion measures of memory, ambulation, and manual dexterity were administered. All RG patients were treated with a 5-day course of Acthar Gel (5 mL/80 IU). Results: In RG patients, SDMT declined from 55.2 to 44.6 at relapse and recovered to 51.7, a slope differing from stable controls ( p  = 0.001). A statistical trend ( p  = 0.07) for the same effect was observed for verbal memory and was significant for ambulation ( p  = 0.03). The Cerebral Function Score from the EDSS also changed in the RG and recovered incompletely relative to controls ( p  = 0.006). Conclusion: These results replicate earlier reports of cognitive worsening during relapse in MS. Clinically meaningful improvements followed relapse on SDMT and ambulation. Cognitive decline during relapse can be appreciated on neurological exam but not patient-reported outcomes.